Chapter 5: Personal Essays about Hearing Stories of Helping - Tsezana-Hyman, Mimica; Katopis, Alexander George; Santiago, Susan (Narrative Works)

(untitled) (Centre for Interdisciplinary Research on Narrative, St. Thomas University, 2019)
This chapter presents three personal stories about the experience of hearing stories of courage and moral choice within the context of family or work environments. These stories range from the retelling of experiences in Greece during the Nazi occupation to stories shared by senior citizens looking back at responses to discriminatory practices in Puerto Rico as they offered shelter and support to the author during Hurricane Katrina. In each case, the stories were either told repeatedly by relatives, or the stories echoed similar stories told in the past by family members. In each of these contexts, the listener describes the experience of learning about moral choices made in challenging situations that have helped to shape the choices that they continue to make long after hearing those stories.